OSELTAMIVIR IN FLU TREATMENT AND PREVENTION AMONG CHILDREN - T.V. Kulichenko; A.S. Darmanyan (Union of pediatricians of Russia, 2007)
The annual vaccination against flu is the most efficient prevention strategy to anticipate this infection, but in many cases, including the vaccinated patients, there is a need in application of the antiviral medications during the seasonal flu breaks. In this article the authors highlight an opportunity to use the oseltamivir neuraminidase inhibitors for the prevention and treatment of flu in children. They also consider the new data on the efficiency and safety of oseltamivir, as well as the potential of its application in the event of a probable flu pandemic.Key words: neuraminidase inhibitors, oseltamivir, flu, children, treatment, prevention.